Challenging Patriarchy and Redefining Women’s Roles - Agustin, Dina; Nurhayati, Sulasih (Pioneer: Journal of Language and Literature, 2025)
This research explores the representation of feminist themes in Chetan Bhagat’s novel One Indian Girl, focusing on the character of Radhika Mehta. Through the lens of Betty Friedan’s liberal feminist theory, the study examines how Radhika embodies feminist ideals by challenging traditional gender roles, pursuing a successful career, and asserting her autonomy. The analysis highlights Radhika’s struggle against societal expectations, her commitment to achieving professional success, and her quest for financial independence. The findings demonstrate that Radhika’s character is a powerful example of feminist empowerment, serving as an inspiration for women to pursue their ambitions and challenge patriarchal norms. This study underscores the importance of education, gender equality, and personal freedom in achieving true feminist empowerment.